The Germanic presence in the provinces of Numidia and Caesarea Mauritania during the Roman period through Latin inscriptions - taourirt, Mustafa (The Algerian Historical Journal, 2026)
The human structure of the ancient Maghreb region knew great ethnic diversity during the Roman period. The region received many peoples and races from different regions of the Roman Empire, whether of a civil or military nature, which formed a mosaic society, Thus, we cannot see societies as a single element, but rather a mixture of local and immigrant races and ethnicities, and among the components of the old Maghreb society, similar to the convergence and fusion of ethnicities among themselves, we find the Germanic element, This aspect generates different aspects of civilization from cultures, customs and traditions, and by returning to the Latin inscriptions "C.I.L" code, some evidence - although few - can be extracted confirming the Germanic presence the provinces of Numidia and Caesarea Mauritania.